Spectrophotometric study of water turbidity for the beverage and food industries of animal origin - Nardy, Jose Fernando [UNESP]; Pereira, Juliano Goncalves [UNESP]; Raghiante, Fernanda; Almeida Nogueira Pinto, Jose Paes de [UNESP]; Biondi, Germano Francisco [UNESP]; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2020)
The determination of water turbidity in the beverage and food industries is extremely important for the final quality of the product. Based on this, the objective of the present work is to evaluate a new alternative methodology to determine the water turbidity of beverage and foods industries through the spectrophotometer at 550 nm using 10 mm optical path methacrylate cuvettes. The amplitude, accuracy, precision, standard curve, cuvettes of different materials (quartz and methacrylate) and comparison of two methods (portable turbidimeter and spectrophotometer at 550 nm) to determine turbidity were analyzed. The main results demonstrated that there are no statistical differences (p>0.05) between the materials of the cuvettes and in the comparison of the methods evaluated for the determination of turbidity in water. We conclude that the determination of turbidity by a spectrophotometer at 550 nm with 10 mm optical path methacrylate cuvettes is a low cost alternative for physicochemical laboratories in the beverage and food industries.
Keywords: cuvettes; spectrophotometry; turbidity; water